IMPLEMENTATION OF TRELLO AS A LEARNING MEDIA IN SOCIAL STUDIES AT JUNIOR HIGH SCHOOLS - Khalda Nisrina Sulistio; Muhammad Ilhamudin; Renaldi Rizki Malizar; Wahyunengsih (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the application of Trello as an educational instrument in Social Studies (IPS) courses in junior high schools. Trello is a collaborative platform that facilitates project-based learning and the development of contemporary skills. Although prior studies indicate that Trello enhances teamwork and student engagement in senior high schools, there remains a paucity of studies regarding its application among junior high school students. This study employed a qualitative case study methodology, using interviews and document analyses of social studies educators in Jakarta. The results showed that Teachers' successful use of Trello was hindered by inadequate knowledge, poor digital infrastructure, and difficulties integrating it into the curriculum. Still, teachers stayed open to the adjustments given direction and assistance. This study proposes enhancing teachers' digital literacy and offering continuous training as a preliminary measure to optimize the use of Trello in social studies education in junior high schools.